Causal mapping for research in information technology - Nakayama, V. K.; Armstrong, Deborah J. (IGI Global (701 E. Chocolate Ave., Hershey, PA, 17033, USA), 2005)
Causal Mapping for Research in Information Technology provides an introduction to causal mapping for IS researchers and practitioners and goes further to provide IS researchers and practitioners information to use in causal mapping for both research and application.